Ontology Model of Telecom Operator Big Data - Globa, L.S.; Novogrudska, R.L.; Koval, A.V. (2018 IEEE International Black Sea Conference on Communications and Networking (BlackSeaCom), 2018)
The paper describes the approach to the representation of telecom operator Big Data by means of ontology model. Big Data characteristics are described as ontology classes, attributes and exemplars that are linked by relations. It was proposed to divide general ontology of telecom operator Big Data into three components: ontology of billing system, ontology of services quality and ontology of monitoring system. In the research all elements of each component are described. Based on ontology searching engine and logical inference is performed.